2024
DOI: 10.1111/jan.16096
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' digital health competence profiles and associated factors: A cross‐sectional study

Erika Jarva,
Anne Oikarinen,
Janicke Andersson
et al.

Abstract: AimsTo identify healthcare professionals' digital health competence profiles and explore associated factors to digital health competence in healthcare settings.DesignA cross‐sectional study.MethodsData were collected from 817 healthcare professionals from nine organizations with an electronic questionnaire by using Digital Health Competence instrument (42 items) and Aspects Associated with Digital Health instrument (15 items) between 1st March and 31st July 2022. K‐means clustering was used to describe digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Additionally, studies such as those by Jarva et al (2024) [37] and Krijgsheld et al (2022) [38] delve into the digital health competence and overall job performance of healthcare professionals, respectively. They underscore the importance of staying abreast of digital advancements and maintaining competence to ensure optimal performance in healthcare delivery.…”
Section: Importance and Location Of The Studymentioning
confidence: 99%
“…Additionally, studies such as those by Jarva et al (2024) [37] and Krijgsheld et al (2022) [38] delve into the digital health competence and overall job performance of healthcare professionals, respectively. They underscore the importance of staying abreast of digital advancements and maintaining competence to ensure optimal performance in healthcare delivery.…”
Section: Importance and Location Of The Studymentioning
confidence: 99%
“…Health care professionals (HCPs) play a pivotal role in the introduction and uptake of DHIs. Previous studies have shown variation in the digital health competence of HCPs [7], and highlighted barriers and facilitators to HCP use of digital health, including infrastructure, technical barriers, training, evidence about technology effectiveness, concerns about workload, and individual personal and psychological barriers, such as resistance to change or concerns about losing human interaction [8]. There has also been some exploration of HCPs attitudes and behaviour in relation to apps for specific conditions such as depression [9]; or patient use of wearables [10].…”
Section: Introductionmentioning
confidence: 97%